Pengaruh Kualitas Audit, Size, Leverage, dan Kepemilikan Keluarga pada Agresivitas Pajak - Astriayu Widyari, Nyoman Yudha; Ketut Rasmini, Ni (E-Jurnal Akuntansi; Vol 27 No 1 (2019), 2019)
This study aims to obtain empirical evidence of the effect of audit quality, size, leverage, and family ownerships on tax aggressiveness. The population of this research is manufacturing company listed on the Indonesia Stock Exchange in 2013-2017. The method of determining sample using non probability sampling method with purposive sampling technique and obtained 125 observations. Data analysis techniques uisng multiple linear regression. The result of analysis shows that audit quality has a negative effect on tax aggressiveness measured by cash effective tax rate (CETR) and has positive effect on tax aggressiveness measured by book tax difference (BTD). Size has a negative effect on tax aggressiveness measured by effective tax rate (ETR) and book tax difference 9BTD). Leverage has a positive effect on tax aggressiveness measured by effective tax rate (ETR). Family ownerships has a positive effect on tax aggressiveness measured by cash effective tax rate. Keywords : audit quality, size, leverage, family ownerships, tax aggressiveness